Femoral artery rupture during total hip arthroplasty - Kakwani, Rajeshkumar (BMJ Publishing Group, 2013)
Vascular injuries are an uncommon but significant complication of total hip arthroplasty. We present a case of femoral artery rupture through an atherosclerotic plaque during primary total hip arthroplasty and a review of the published literature. The early recognition and prompt treatment of this complication can reduce the mortality and morbidity associated with this injury.